The The Influence of Product Quality, Service Quality, and Social Media Marketing on Customer Satisfaction - Fauziah, Syifa; L Siahaan, Sinthon (Dinasti International Journal of Management Science, 2025)
This study aims to examine the impact of product quality, service quality, and social media marketing on customer satisfaction at The Coffee Bean & Tea Leaf outlet. The research adopts a quantitative approach with a causal method. A total 100 respondents were selected using purposive sampling-specifically, customes who had visited the outlet at least twice within the last three months and followed The Coffee bean & Tea Leaf’s official social media account. Data were collected trough questionnaires and analyzed using multiple linear regression after passing classical assumption tests, including normality, heteroscedasticity, multicollinearity, and linearity. The result indicate the product quality, service quality, and social media marketing have a positive and significant effect on customer satisfaction, both partially and simultaneously. Among the three variables, service quality contributes the most. The coefficient of determination (R²) value of 0,442 indicates that the three independent variables explain 44,2% of the variation in customer satisfaction. These finding highlight the importance of maintaining product quality, providing excellent service, and utilizing social media effectively to build positive relationships with customer.